2012
DOI: 10.4049/jimmunol.1002346
|View full text |Cite
|
Sign up to set email alerts
|

E2A and CBP/p300 Act in Synergy To Promote Chromatin Accessibility of the Immunoglobulin κ Locus

Abstract: V(D)J recombination of Ig and TCR genes is strictly regulated in a lineage- and stage-specific manner by the accessibility of target gene chromatin to the recombinases RAG1 and RAG2. It has been shown that enforced expression of the basic helix–loop–helix protein, E2A, together with RAG1/2 in a nonlymphoid cell line BOSC23 can induce V(D)J recombination in endogenous Igκ and TCR loci by increasing chromatin accessibility of target gene segments. In this study, we demonstrate that ectopically expressed E2A prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 50 publications
(76 reference statements)
1
26
0
Order By: Relevance
“…E2A proteins have been particularly well studied for their roles in antigen receptor assembly 35,36 . Enforced expression of the E2A encoded isoform, E47, readily promotes the assembly of antigen receptor genes in embryonic kidney cells 37,38 . We previously noted that a significant fraction of the V κ regions were located within close genomic proximity from E2A binding sites 39 .…”
Section: Discussionmentioning
confidence: 99%
“…E2A proteins have been particularly well studied for their roles in antigen receptor assembly 35,36 . Enforced expression of the E2A encoded isoform, E47, readily promotes the assembly of antigen receptor genes in embryonic kidney cells 37,38 . We previously noted that a significant fraction of the V κ regions were located within close genomic proximity from E2A binding sites 39 .…”
Section: Discussionmentioning
confidence: 99%
“…When bound to the Eκ i , E2A recruits the transcriptional co-activators CREB-binding protein (CBP) and p300, which modify nucleosomal histones in the flanking Cκ and Jκ regions with acetyl groups, thereby making the region accessible to the recombination machinery 17,136,137 . In addition to E2A, the pre-BCR induces expression of the interferon regulatory factor (IRF) family members IRF4 and IRF8, which are required in vivo for initiating Igκ gene recombination, suppressing the SLC and exiting the cell cycle 138,139 .…”
Section: Pre-bcr Signalling and Igκ Recombinationmentioning
confidence: 99%
“…The p300 protein is known as an important transcription coactivator that is able to bind to many transcription factors, such as p53, c-jun and IRF-1, and acetylate these transcription factors, and then regulate cell growth, differentiation and apoptosis. 32, 34, 35, 36, 37 Our previous microarray analyses revealed that the expression of transcription coactivator p300 was obviously upregulated at 3 h both in vivo (5.9-fold) and in vitro (14.3-fold). However, the role of p300 in mediating IRF-1 acetylation and its ability to promote XAF1 gene activation as well as cellular apoptosis in GMCs triggered by sublytic C5b-9 in Thy-1N rats need to be elucidated.…”
mentioning
confidence: 93%